1-Methylnicotinamide attenuates lipopolysaccharide-induced cognitive deficits via targeting neuroinflammation and neuronal apoptosis - Mu, Rong-hao; Tan, Yuan-zhi; Fu, Li-li; Nazmul Islam, Mohammad; Hu, Mei; Hong, Hao; Tang, Su-su (International immunopharmacology, 2019)
•1-Methylnicotinamide improves LPS-induced memory impairment in mice.•1-Methylnicotinamide inhibits LPS-induced neuroinflammatory response in the hippocampus and frontal cortex.•1-Methylnicotinamide inhibits LPS-induced glial cells activation in the hippocampus and frontal cortex.•1-Methylnicotinamide inhibits LPS-induced neuronal apoptosis in the hippocampus and frontal cortex. Alzheimer’s disease (AD) is a neurodegenerative disease that affects cognition and behavior. The neuroinflammatory response in the brain is an important pathological characteristic in AD. In this study, we investigated the neuroprotective effects of 1-Methylnicotinamide (MNA), known as the main metabolite of nicotinamide, on reducing lipopolysaccharide (LPS)-induced cognitive deficits via targeting neuroinflammation and neuronal apoptosis. We found that the mice treated with LPS exhibited cognitive deficits in the novel object recognition, Morris water maze and Y-maze avoidance tests. However, intragastric administration of MNA (100 or 200 mg/kg) for 3 weeks significantly attenuated LPS-induced cognitive deficits in mice. Importantly, MNA treatment suppressed the protein expression of nuclear factor-kappa B p65 (NF-κB p65), pro-inflammatory cytokines (TNF-α, IL-6) and decreased the activation of microglia and astrocytes in the hippocampus and frontal cortex of LPS-induced mice. In addition, MNA treatment suppressed neuronal apoptosis by reducing the number of TUNEL-positive cells, caspase-3 activation and increasing the level of Bcl-2/Bax ratio in the hippocampus and frontal cortex. These findings indicate that MNA could be a potential neuroprotective drug in neurodegenerative diseases such as AD.